Pengaruh Sistem Pengendalian Internal dan Whistleblowing System terhadap Pencegahan Fraud Pengadaan Barang dan Jasa - Silmi Syifa Syafitri; Syafdinal Syafdinal (Owner : Riset dan Jurnal Akuntansi, 2023)
The background of this research is that the procurement of goods and services has a high level of vulnerability to allow inefficiencies and ineffectiveness to occur and become a venue for fraud, one of which is the practice of bribery. The purpose of this research is to find out whether the Internal Control System and Whistleblowing System impact on prevention Fraud Procurement of goods and services at two state-owned companies in the city of Bandung. The research method used is quantitative research with a survey approach. The population in this study were employees of the Internal Control Unit Division, the Procurement Division and the Accounting Division at PT Pindad (Persero) and PT Dirgantara Indonesia (Persero). The results of the research show that the internal control system and whistleblowing system effect on prevention fraud procurement of goods and services either partially or simultaneously. The conclusion of this research is the higher the level of the Internal Control System and the Whistleblowing System, the higher the level of Goods and Services Procurement Fraud Prevention.